2023
DOI: 10.3389/feart.2023.1115054
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the simultaneous fracture propagation from multiple perforation clusters in horizontal wells using 3D block discrete element method

Abstract: Multi-cluster horizontal well fracturing is one of the key technologies to develop the unconventional reservoirs such as shales. However, the field data shows that some perforation clusters have little production contribution. In this study, a three-dimensional (3D) numerical model for simulating the multiple fracture propagation based on 3D block discrete element method was established, and this model considers the stress interference, perforation friction and fluid-mechanical coupling effect. In order to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Huang performed simulation to study the interaction between hydraulic fractures and gravels in glutenite formation based on 2D particle discrete element method, and results showed that the non-uniformly distributed stress field caused by the existence of glutenite maily affects the fracture propagating path (Huang et al, 2023b). Although the reservoir types studied are different and the methods used are also varied, these studies have reached similar conclusions regarding the expansion behavior of hydraulic fractures in fractured reservoirs (Song et al, 2017;Tan et al, 2017;Huang et al, 2019;Song et al, 2020;Tan et al, 2020;He et al, 2023;Liu et al, 2023;Wu et al, 2023). They all agreed the significant influence of reservoir heterogeneity and geostress states on the propagation path of hydraulic fractures, as well as the control effect of fracturing fluid flow rate and viscosity on the morphology of hydraulic fracture propagation.…”
Section: Frontiers In Energy Researchmentioning
confidence: 96%
“…Huang performed simulation to study the interaction between hydraulic fractures and gravels in glutenite formation based on 2D particle discrete element method, and results showed that the non-uniformly distributed stress field caused by the existence of glutenite maily affects the fracture propagating path (Huang et al, 2023b). Although the reservoir types studied are different and the methods used are also varied, these studies have reached similar conclusions regarding the expansion behavior of hydraulic fractures in fractured reservoirs (Song et al, 2017;Tan et al, 2017;Huang et al, 2019;Song et al, 2020;Tan et al, 2020;He et al, 2023;Liu et al, 2023;Wu et al, 2023). They all agreed the significant influence of reservoir heterogeneity and geostress states on the propagation path of hydraulic fractures, as well as the control effect of fracturing fluid flow rate and viscosity on the morphology of hydraulic fracture propagation.…”
Section: Frontiers In Energy Researchmentioning
confidence: 96%
“…For geostress, many theories, methods, and applications are still in the exploratory stage (Yang et al, 2013;Song et al, 2017;Song et al, 2020;Liu et al, 2023). Geostress is a key factor affecting shale hydraulic fracturing design (Huang et al, 2019;Zheng et al, 2022;Huang et al, 2023a;He et al, 2023;Tan et al, 2023). Meanwhile, understanding geostress is a prerequisite for successful development of shale gas (Tan et al, 2017;Luo et al, 2022;Zhang et al, 2022;Huang et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of numerical methods and computer technology provides an effective way to study hydraulic fracture propagation in large-scale low-permeability reservoirs and compensates for the shortcomings of experimental research. In recent years, many researchers have employed numerical methods to create large-scale three-dimensional (3D) fracturing models to study the behavior of fracture propagation during multiple horizontal well fracturing. , The effects of well spacing, perforation parameters, fracturing sequences, and horizontal stress differences on fracture propagation have provided a theoretical basis for optimizing horizontal well cluster spacing. Large-scale fracturing models effectively solve the problem of size bottlenecks in the experimental specimens. Research on the fracture propagation law based on large-scale models can contribute to a better understanding of the mechanism of hydraulic fracture propagation in the field. …”
Section: Introductionmentioning
confidence: 99%
“…24−26 In recent years, many researchers have employed numerical methods to create large-scale three-dimensional (3D) fracturing models to study the behavior of fracture propagation during multiple horizontal well fracturing. 27,28 The effects of well spacing, perforation parameters, fracturing sequences, and horizontal stress differences on fracture propagation have provided a theoretical basis for optimizing horizontal well cluster spacing. 29−34 Large-scale fracturing models effectively solve the problem of size bottlenecks in the experimental specimens.…”
Section: Introductionmentioning
confidence: 99%